2015
DOI: 10.2147/opth.s75812
|View full text |Cite
|
Sign up to set email alerts
|

Refractive outcomes of an advanced aspherically optimized profile for myopia corrections by LASIK: a retrospective comparison with the standard aspherically optimized profile

Abstract: PurposeA retrospective comparison of refractive outcomes of a new, aspherically optimized profile with an enhanced energy correction feature (Triple-A) and the conventionally used aspherically optimized profile (ASA, or aberration smart ablation) for correction of low-to-high myopia.SettingAugen-OP-Centrum, Cologne, GermanyDesignRetrospective nonrandomized comparative studyMethodsA central database at the Augen-OP-Centrum was used to gather retrospective data for low-to-high myopia (up to −10 D). One hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 21 publications
1
6
0
Order By: Relevance
“…The enhanced energy correction in the Triple-A profile is stronger than that of ASA and TSA profiles. In two reports, this achieved better predictability compared with the ASA profile after LASIK and photorefractive keratectomy (PRK) [7, 8]. In our study we demonstrated better predictability achieved with the MEL 90 and Triple-A profile than with the MEL 80 and TSA profile after LASEK.…”
Section: Discussionsupporting
confidence: 64%
“…The enhanced energy correction in the Triple-A profile is stronger than that of ASA and TSA profiles. In two reports, this achieved better predictability compared with the ASA profile after LASIK and photorefractive keratectomy (PRK) [7, 8]. In our study we demonstrated better predictability achieved with the MEL 90 and Triple-A profile than with the MEL 80 and TSA profile after LASEK.…”
Section: Discussionsupporting
confidence: 64%
“…This program was designed to maintain the prolate shape of the cornea from −3 to −6 D of sphere correction. 42 , 43 In addition, the wavefront-guided LASIK program was applied for all cases in the LASIK group; SMILE does not have such a program. If an aspheric lenticule or a wavefront-guided lenticule creation protocol was available for SMILE surgery, the difference between the SMILE and LASIK groups could potentially be larger.…”
Section: Discussionmentioning
confidence: 99%
“…Gatinel et al 14 In later studies, many groups reported findings favoring an aspherically optimized ablation profile over the conventional profiles in terms of most postoperative refractive outcomes. [17][18][19] In a large-scale study including 400 eyes (200 eyes in the wavefront-optimized group and 200 eyes in the custom-Q group), Tawfik et al 20 reported a statistically significant difference in postoperative change in Q-values (P = .02) and postoperative visual acuity (P = .42) between the two groups.…”
Section: Discussionmentioning
confidence: 99%